1990
DOI: 10.1056/nejm199002153220704
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Crises in Hereditary Tyrosinemia

Abstract: Hereditary tyrosinemia results from an inborn error in the final step of tyrosine metabolism. The disease is known to cause acute and chronic liver failure, renal Fanconi's syndrome, and hepatocellular carcinoma. Neurologic manifestations have been reported but not emphasized as a common problem. In this paper, we describe neurologic crises that occurred among children identified as having tyrosinemia on neonatal screening since 1970. Of the 48 children with tyrosinemia, 20 (42 percent) had neurologic crises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(111 citation statements)
references
References 26 publications
0
107
0
4
Order By: Relevance
“…FAH activity was assayed spectrophotometrically using acetopyruvate (AP) (Sigma Chemical Co.) and fumarylacetoacetate (FAA) prepared enzymatically from homogentisic acid (Sigma) as described previously (17,18,30). Assays were initiated by adding recombinant His-tagged FAH to reaction mixtures that covaried AP (0.625, 0.833, 1.25, 2.5, and 5.0 mM) with HMPOBA (0.0, 250, 500, and 750 M) or covaried FAA (3,8, and 15 M) with HMPOBA (0, 125, 250, 500, or 750 M). The disappearance of AP and FAA was followed at 292 and 330 nm for 2-3 min at 37°C, respectively.…”
Section: Kinetic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…FAH activity was assayed spectrophotometrically using acetopyruvate (AP) (Sigma Chemical Co.) and fumarylacetoacetate (FAA) prepared enzymatically from homogentisic acid (Sigma) as described previously (17,18,30). Assays were initiated by adding recombinant His-tagged FAH to reaction mixtures that covaried AP (0.625, 0.833, 1.25, 2.5, and 5.0 mM) with HMPOBA (0.0, 250, 500, and 750 M) or covaried FAA (3,8, and 15 M) with HMPOBA (0, 125, 250, 500, or 750 M). The disappearance of AP and FAA was followed at 292 and 330 nm for 2-3 min at 37°C, respectively.…”
Section: Kinetic Assaysmentioning
confidence: 99%
“…HT1 is an autosomal recessive disease with an acute form that causes death in infancy due to liver failure and a chronic form that causes an early age death due to hepatocellular carcinoma, liver cirrhosis, and neurologic crises (2,3). The lethal nature of HT1 is most likely due to the accumulation of the toxic intermediate fumarylacetoacetate in the absence of FAH activity (4 -6).…”
mentioning
confidence: 99%
“…Önenli Mungan et al (24) and Schlump et al (25) reported that interruption of nitisinone treatmentcan cause severe neurological crisis inpatients with HTI. These crises occur in up to 50% of untreated children and these are one of the major causes of mortality (5,26). In follow up, regular abdominal USG was performed every 6-12 months and AFP levels, plasma amino acids and urine succinylacetone were checked every 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Fanconi syndrome with renal tubular acidosis may develop; and with the accumulation of the secondary metabolite, succinylacetone (4,6: dioxoheptanoate, a potent inhibitor of 5-aminolaevulinate dehydratase), neurovisceral episodes mimicking acute porphyria occur (Mitchell et al 1990(Mitchell et al , 2001Sassa and Kappas 1983).…”
Section: Sharing Amongst Orphans In the Tyrosine Degradation Disordersmentioning
confidence: 99%